(untitled) (Conference Zone, 2022)
goal is a consciously planned outcome of teaching and learning a foreign language and its native culture. Depending on the learning environment, a specific goal is set. The concept of conditions includes the type of educational institution, the psychological characteristics of the student, language experience, the time allocated to the subject. In the system of continuing education, special attention is paid to language learning. In today’s market economy and the development of information technology, the need for learning a foreign language is growing